Invited Mini-Review Research Topic: Utilization of Protoplasts to Facilitate Gene Editing in Plants: Schemes for In Vitro Shoot Regeneration From Tissues and Protoplasts of Potato and Rapeseed: Implications of Bioengineering Such as Gene Editing of Broad-Leaved Plants - Andreasson, Erik; Kieu, Nam Phuong; Zahid, Muhammad Awais; Carlsen, Frida Meijer; Marit, Lenman; Sandgrind, Sjur; Petersen, Bent Larsen; Zhu, Li-Hua (Frontiers in Genome Editing, 2022)
Schemes for efficient regeneration and recovery of shoots from in vitro tissues or single cells, such as protoplasts, are only available for limited numbers of plant species and genotypes and are crucial for establishing gene editing tools on a broader scale in agriculture and plant biology. Growth conditions, including hormone and nutrient composition as well as light regimes in key steps of known regeneration protocols display significant variations, even between genotypes within the same species, e.g. potato (Solanum tuberosum). As fresh plant material is a prerequisite for successful shoot regeneration, plant material often needs to be refreshed for optimizing growth and physiological state prior to transformation. Protoplast has become an important approach for obtaining transgene free edited plants by genome editing, CRISPR/Cas9. In this approach, callus formation from protoplasts is induced by one set of hormones, followed by organogenesis, i.e. shoot formation, which is induced by a second set of hormones. Requirements on culture conditions at these key steps vary considerably between species and genotypes, which often require quantitative adjustments of medium compositions. In this mini-review, we outline protocols for clonal regeneration and cultivation from single cells, particularly protoplasts in potato and rapeseed. We focus mainly on different hormone treatment schemes, and highlight the importance of medium compositions, e.g. sugar, nutrient, and light regimes as well as culture durations at the key regeneration steps. We believe that this review would provide important information and hints for establishing efficient regeneration strategies from other closely related and broad-leaved plant species in general.